2017
DOI: 10.1021/acs.langmuir.7b00386
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Energy Ion Scattering Approach for Studying Au Nanoclusters Grown on an H2O Buffer Layer

Abstract: Impact collision ion scattering spectroscopy (ICISS), which is a variation of low energy ion scattering (LEIS) that employs large scattering angles, is performed on Bi 2 Se 3 surfaces prepared by ion bombardment and annealing (IBA). ICISS angular scans are collected experimentally and simulated numerically along the [120] and [120] azimuths, and the match of the positions of the flux peaks shows that the top three atomic layers are bulk-terminated. A newly observed feature is identified as a minimum in the m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…This is because the alkali LEIS technique is adept for studying surfaces composed of multiple elements and can address questions about the charge state of those elements. Previous results have shown that the ions scattered from Au and Ag nanoclusters on an oxide and other substrates have a much higher neutralization probability than those scattered from the bulk metal, and that neutralization decreases as the cluster size increases [48][49][50][51][52][53][54][55]. Although it is possible that the alkali LEIS neutralization rate and the Au nanocluster catalytic activity are related, such a correlation has not yet been confirmed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the alkali LEIS technique is adept for studying surfaces composed of multiple elements and can address questions about the charge state of those elements. Previous results have shown that the ions scattered from Au and Ag nanoclusters on an oxide and other substrates have a much higher neutralization probability than those scattered from the bulk metal, and that neutralization decreases as the cluster size increases [48][49][50][51][52][53][54][55]. Although it is possible that the alkali LEIS neutralization rate and the Au nanocluster catalytic activity are related, such a correlation has not yet been confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…To explain the unusually high neutralization for alkali ions scattered from small Au nanoclusters, a model is developed here based on the notion that the charge associated with each Au atom in a cluster is different. Previously, the charge on the Au clusters had been considered in aggregate when analyzing ion neutralization [48][49][50][51][52][53][54][55], but the present model is dependent on the differences in charge between the atoms and not on the average charge. Density functional theory (DFT) calculations performed for Au nanoclusters supported on TiO2 find that the charge associated with the edge atoms of the nanocluster are noticeably different from the center atoms [27,31].…”
Section: Introductionmentioning
confidence: 99%